Radiocarbon ages of sediment core samples from the Bay of Bengal (IEDA: EarthChem Library)
This dataset is a compilation of new and previously reported results from accelerator mass spectrometry (AMS) radiocarbon dating of planktonic foraminifera from sediment core samples collected during cruise SO93 on R/V Sonne in the Bay of Bengal. These data are used to create an age model for the sediment cores.